Capabilities for circularity: Overcoming challenges to turn waste into a resource. (25th January 2022) - Wade, Belinda; Meath, Cristyn; Griffiths, Andrew
Abstract: Although designing out waste is a core principle of the circular economy, in established companies, waste may not easily be designed out requiring innovation to develop alternative, value creating, uses for the waste material. This article presents a longitudinal, empirical study of the SME Rock Trade Industries, a company focused on sustainability in the quarrying sector, seeking to achieve zero waste of their extracted resource. Capabilities enabling the creation of products from the company's waste are examined through qualitative analysis, within established categories of sensing, seizing and reconfiguration. Our research highlights the importance of capabilities in innovation, experimentation, research and development, and stakeholder connections in reconceptualising waste as a resource. Presenting a model of the capability development over time, we proposed the strength of the desire to create change combined with the deviation of the desired change from the marketplace determine the set of dynamic capabilities required.